Aquatic Adaptation and Depleted Diversity: A Deep Dive into the Genomes of the Sea Otter and Giant Otter. (18th June 2019) - Beichman, Annabel C; Koepfli, Klaus-Peter; Li, Gang; Murphy, William; Dobrynin, Pasha; Kliver, Sergei; Tinker, Martin T; Murray, Michael J; Johnson, Jeremy; Lindblad-Toh, Kerstin; Karlsson, Elinor K; Lohmueller, Kirk E; et al.
Abstract: Despite its recent invasion into the marine realm, the sea otter ( Enhydra lutris ) has evolved a suite of adaptations for life in cold coastal waters, including limb modifications and dense insulating fur. This uniquely dense coat led to the near-extinction of sea otters during the 18th–20th century fur trade and an extreme population bottleneck. We used the de novo genome of the southern sea otter ( E. l. nereis ) to reconstruct its evolutionary history, identify genes influencing aquatic adaptation, and detect signals of population bottlenecks. We compared the genome of the southern sea otter with the tropical freshwater-living giant otter ( Pteronura brasiliensis ) to assess common and divergent genomic trends between otter species, and with the closely related northern sea otter ( E. l. kenyoni ) to uncover population-level trends. We found signals of positive selection in genes related to aquatic adaptations, particularly limb development and polygenic selection on genes related to hair follicle development. We found extensive pseudogenization of olfactory receptor genes in both the sea otter and giant otter lineages, consistent with patterns of sensory gene loss in other aquatic mammals. At the population level, the southern sea otter and the northern sea otter showed extremely low genomic diversity, signals of recent inbreeding, and demographic histories marked by population declines. These declines may predate the fur trade and appear to have resulted in an increase in putatively deleterious variants that could impact the future recovery of the sea otter.